David and his theologian: literary, social, and theological investigations of the early monarchy - Brueggemann, Walter (Cascade Books, 2011)
Throughout Walter Brueggemann's career, he has repeatedly found his way back to the David and royal traditions. From some of his earliest articles and essays to monographs, commentaries, and sermons, he has explored this rich field in literary, social, and theological depth. As he has said, "My preoccupation with David rests on the awareness that David occupies a central position in the imagination of ancient Israel and in the rendering of 'faith and history' by that community. As the genealogies locate David, he stands mid-point between the rigors of Mosaic faith and the destruction of Jerusalem; as a consequence he becomes, in the artistry of Israel, the carrier of all the ambivalence Israel knew about guarantees and risks in the world YHWH governs." This volume brings together some of Brueggemann's key essays on the David traditions, as well as their interrelationships with traditions in the book of Genesis--Foreword